Application of Barcelona test for controlling energy absorption capacity of FRS in underground mining works. (20th June 2020) - Carmona, Sergio; Molins, Climent; García, Sergio
Graphical abstract: Highlights: A correlation between square panel test and Barcelona test has been developed. The application of correlation to a concrete sprayed on-site has proven satisfactory. Smaller specimens simplify and improve the quality control of the tunnels' support. Abstract: In recent years in Chile, the use of fiber reinforced shotcrete (FRS) has been widely extended in underground works, particularly in tunnels for roads, mines and hydroelectric projects. In these projects, the design of the supports is mainly based on the modified Q–Barton method, which relates the rock mass quality to the minimum energy absorption capacity of the FRS, which is determined by the square panel test, with panels filled during spraying. However, to obtain these specimens, complex procedures must be followed both on-site and, in the laboratory, and the results obtained present a large scatter. To improve the execution control of the FRS lining of tunnels, an empirical correlation has been developed between the square panel test of a synthetic-fiber reinforced concrete and the double-punch Barcelona test of cylinders, at laboratory level. The application of such a correlation to a concrete sprayed on-site using the same fiber has proven satisfactory, with a maximum difference between the experimental and the correlated measurement of 9.9%. Then, the methodology presented in this paper can be applied to control the FRS to any other case.